2017
DOI: 10.1002/aic.16014
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing CO2 absorption efficiency using a novel PTFE hollow fiber membrane contactor at elevated pressure

Abstract: The internal structure design of membrane module is very important for gas removal performance using membrane contactor via physical absorption. In this study, a novel membrane contactor developed by weaving polytetrafluoroethylene (PTFE) hollow fibers was applied to remove CO 2 from 60% N 2 1 40% CO 2 mixture (with CO 2 concentration similar to that of biogas) at elevated pressure (0.8 MPa) using water as absorbent. Compared with the conventional module with randomly packed straight fibers, the module with wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In the past decades, extensive lab‐scale studies have been reported on membrane absorption (MA) for CO 2 capture using various membrane materials, such as polypropylene (PP) 4 and polytetrafluoroethylene (PTFE), 5–8 and chemical solvents, such as monoethanolamine (MEA), 4 and 4‐diethylamino‐2‐butanol (DEAB) 9 . In addition, some effective approaches are used to reduce the mass transfer resistance of membrane element, such as preparing membranes with notable hydrophobicity (to prevent membrane wetting) 10 and with asymmetric structure (to increase permeability) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, extensive lab‐scale studies have been reported on membrane absorption (MA) for CO 2 capture using various membrane materials, such as polypropylene (PP) 4 and polytetrafluoroethylene (PTFE), 5–8 and chemical solvents, such as monoethanolamine (MEA), 4 and 4‐diethylamino‐2‐butanol (DEAB) 9 . In addition, some effective approaches are used to reduce the mass transfer resistance of membrane element, such as preparing membranes with notable hydrophobicity (to prevent membrane wetting) 10 and with asymmetric structure (to increase permeability) 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The membrane material is crucial to a membrane contactor. Commercial membrane materials include organic membranes, mixed matrix membranes, , ceramic membranes, , etc. Ceramic membranes with the advantages of high mechanical strength and chemical stability are propitious for withstanding high-temperature and corrosive ship exhaust .…”
Section: Introductionmentioning
confidence: 99%
“…Among the materials above, PTFE has attracted much attention in recent years 11 . Thanks to its unique properties including excellent chemical resistance, thermal stability, and hydrophobicity, 12 PTFE membranes have great potential in membrane distillation, 13–15 MBR wastewater treatment, 16 CO 2 absorption, 17–19 absorbent regeneration, 20 bromine enrichment from brine, 21 PM2.5 removal, 22 and so forth.…”
Section: Introductionmentioning
confidence: 99%